Expansion of Local Micro, Small and Medium Enterprises (MSMEs) Market Through the Development of Tourism Villages - Mastuki Mastuki; Anita Asnawi; Galuh Ajeng Ayuningtyas; Andry Herawati (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study discusses the strategy of expanding the local Micro, Small, and Medium Enterprises (MSMEs) market through the development of Tourism Villages as a solution to limited market access and low competitiveness of MSME actors. MSMEs in Indonesia often face obstacles in aspects of the marketing mix such as venues, prices, products, and promotions. Through a qualitative approach, this study analyzes the direct impact of Tourism Villages on increasing market access, product innovation, and the role of innovation diffusion in encouraging technology adoption by MSME actors. The results of the study show that Tourism Villages such as Pujon Kidul, Taman Sari, and Sokobanah Daya are able to become a catalyst for the local economy by attracting tourists as potential consumers, reducing operational costs, and creating an innovation ecosystem that supports the growth of MSMEs. BUMDes (Village-Owned Enterprises) play an important role in digital promotion, product packaging development, and strengthening the capacity of local business actors through training and mentoring programs. Moreover, Tourism Villages encourage collaboration between stakeholders such as village governments, educational institutions, and private sectors in building sustainable local entrepreneurship. They also facilitate knowledge sharing and cultural preservation while integrating economic, social, and environmental values. Although there are still challenges such as lack of managerial skills, limited access to capital, and dependence on tourism seasons, the potential for long-term impact remains high. This study concludes that the integration of Tourism Village development with MSME strengthening strategies can be a model for inclusive and sustainable village economic empowerment. These findings provide practical recommendations for village governments, BUMDes managers, and MSME actors in building effective synergies that accelerate local economic growth and resilience.